How did a quality premium financial incentive influence antibiotic prescribing in primary care? Views of clinical commissioning group and general practice professionals - Borek, AJ; Anthierens, S; Allison, R; McNulty, CAM; Lecky, DM; Costelloe, C; Holmes, A; Butler, CC; Walker, AS; Tonkin-Crine, S (Oxford University Press, 2020)
Background: The Quality Premium (QP) was introduced for Clinical Commissioning Groups (CCGs) in England to optimize antibiotic prescribing, but it remains unclear how it was implemented.